Sexual health outcomes for young people in state care: Cross-sectional analysis of a national survey and views of social care professionals in Wales. (June 2018) - Roberts, Louise; Long, Sara Jayne; Young, Honor; Hewitt, Gillian; Murphy, Simon; Moore, Graham F.
Abstract: This paper draws upon data from two separate studies to consider sexual health outcomes for young people in state care in Wales. Cross sectional analysis of the School Health Research Network Survey (2015) examined sexual health behaviours and outcomes of young people in foster care compared to those living in private households. The findings are contextualised with qualitative data (collected 2016) from social care professionals about their practice experiences of supporting sexual health development and seeking to prevent early pregnancy for young people in state care. Findings suggest that young people in state care in Wales experience poorer sexual health outcomes compared to those not in care. Insights from professionals suggest that whilst the state care system has the potential to identify and respond to young people's needs, its effectiveness can be compromised by issues of resources, value-based judgements related to the age at which young people could and should be sexually active, and individual choice and determinism. It is suggested that statutory monitoring of sexual health related outcomes is required, together with a review of policy and practice 'with', rather than 'for', young people in state care. Finally it is argued that increased attention on the quality as well as the quantity of relationships young people in state care have with carers and professionals may provide a simple but powerful policy approach in continued efforts to secure parity in respect of sexual health and development. Highlights: Paper examines sexual health outcomes for young people in state care in Wales. Finds that young people in state care experience poorer outcomes compared to those not in care. Insights from professionals suggest that the care system has the potential to identify and respond to young people's needs. The effectiveness of the system can be hindered by insufficient resources, value-based judgements and individual choice.